Isidingo as entertainment-education - Nadia van der Merwe (Communicare)
In developing countries, the popular media can be used effectively to address social problems (Vaughan, Rogers, Singhal & Swalehe, 2000:82). In recent decades, various developmental, educational and other socially useful messages have often been included in the content of soap operas (Mody, 1991). The producers of South African soap opera Isidingo are acutely aware of their social responsibility and therefore attempt to make a contribution towards social change and nation building. As such, Isidingo employs positive role models to transmit pro-social messages to its viewers. This paper will report on a study that explored the application of the entertainment-education (E-E) strategy in the local soap opera Isidingo by investigating the perceptions of female viewers in respect of self-reported knowledge acquisition, attitudes and behavioural changes due to watching this programme.